Community-acquired vancomycin-resistant enterococcus faecium: a case of infective endocarditis. - Kamarudin, Norhidayah; Ismail, Zalina (2018)
Vancomycin-resistant enterococcus (VRE) is gaining reputation as a significant nosocomial pathogen and becoming a major cause of public health concern. E. faecium constitute approximately 90% of the isolated VRE strains (John et. al. 2015). Malaysia was spared until almost two decades ago, the first case of VRE isolation from clinical specimen was reported in one of the country’s major referral hospital (Riley et. al. 1996). It is particularly alarming since the resistance rate of local clinical E. faecium isolates towards vancomycin exhibit an increasing trend with the latest rate being at 14.9% (IMR 2016). Local and global data on severe VRE infection acquired from the community is extremely limited. Hence, we report a potential rare case of community-acquired VRE endocarditis-related bacteremia and challenges encountered in managing such infection.